Highsmith's The Price of Salt: A Harbinger of Homosexual's Happiness - Pokharel, Bhawana (JODEM: Journal of Language and Literature, 2019)
Patricia Highsmith’s The Price of Salt embodies homosexual relationship between its female characters namely Therese and Carole. In doing so, it presents a resistance to the contemporary heterosexual society which accepts only heterosexuality as its sexual norm. The article argues that the character’s rejection of the traditional mode of heterosexual relationship is in order to search for their lesbian self though that is taken as a deviation in the society; and so it faces various challenges. However, the characters together overcome the obstacles laid down by the society and move forward to finding freedom as well as establishing a new path which is taken as an unconventional practice in the then society; in turn, it proves to be the harbinger of hope and happiness for their kind. To substantiate this claim, the article draws from Lillian Faderman, Adrienne Rich, Judith Butler and Helen Boyd for the different aspects of lesbianism and queer theory they present. Similarly, the article is a descriptive, interpretive and analytical reading of the novel on the basis of the ideas based on the above mentioned scholars.